(untitled) (Iraqi Journal of Medical Sciences, 2004)
Objectives: The aim of this study is to determine the preliminary epidemiologic and pathologic features of the tumor, to review patterns of presentation, to present operative management and compared to current international standards. Subjects & Methods: The records of 94 patients with colorectal and anal canal tumors presented to our unit in the third floor of Al-Kadhimiya Teaching Hospital, between 1995-2002 were reviewed and analyzed regarding age, sex, tumor site, histopathology, degree of differentiation, stage (Duke) and type of operations. Results: Fifty six (60%) patients were males and 38 (40%) females; male to female ratio was 1.5:1. The peak age incidence was between 40-50 years (30.85%) with 23 (24.46%) patients were under the age of 40 years. The commonest presenting symptom was bleeding per rectum, followed by change in bowel habits. The rectum was the most common anatomical site affected. The most common histopathological type was adenocarcinoma. Most of the tumors were moderately differentiated. The majority of tumors at presentation were in Duke stage B and C. The two most common operations performed were abdominoperineal resection and right hemicolectomy Conclusion: • Colorectal cancer is not as uncommon in Iraq as has been believed, and the incidence could well be increasing, especially since the life style is rapidly becoming more westernized. • There is a particularly high incidence in younger people and for pathologically aggressive tumors. • Health education, especially of the warning signs of cancer, and increased awareness of the seriousness of the disease, both among the public and medical practitioners are essential for early diagnosis. • Any screening program, if started, may need to start at a younger age group. Key words: colorectal malignancies, epidemiology, pathology, presentation, surgery. Iraqi J Med Sci, 2004; Vol. 3 (1): 73-76